Anti-Platelet Efficiency of Cryopreserved Placental Extracts in Alginate Carriers - Narozhny, Stanislav V.; Bobrova, Elena N. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):180.